THE CONCEPT OF IMAGO DEI IN THE THOUGHT OF GERRIT CORNELIS BERKOUWER - Farlen Tatukude; Billy Kristanto (VERBUM CHRISTI JURNAL TEOLOGI REFORMED INJILI, 2019)
Gerrit Cornelis Berkouwer was a significant Dutch Reformed theologian. This article will observe Berkouwer’s concept of imago Dei based on systematic-biblical method. In other words, biblical concept will only support the systematic-theological based discussion. It will be demonstrated through this article that, in comparison to previous approaches of explaining the concept of the image, Berkouwer had made a significant contribution. That contribution is found in his emphasis on the functional aspect of being the image. In doing this, on one hand, he followed the path of Reformatory tradition, but on the other hand, he also diverted from the Reformatory tradition on some issues about the concept of the image. KEYWORDS: Berkouwer; imago Dei; human nature; human dignity; Postmodernism; analogia entis; analogia relationis; analogia amoris